H2 production from catalytic dry reforming of landfill gas utilizing membrane reactor with combined heat and power system: 3E (energy, economic and environmental) feasibility analysis. (1st November 2021) - Lim, Dongjun; Byun, Manhee; Lee, Boreum; Lee, Aejin; Kim, Ayeon; Brigljević, Boris; Lim, Hankwon
Highlights: Two different process configurations for H2 production from LFG were proposed. Comprehensive process simulation was performed using Aspen Plus®. CDR in MR is superior to a conventional chemical reactor at the same temperature. Requirements for MR to compete with high-temperature operation were identified. Abstract: For utilization of valuable raw material of landfill gas (LFG), CH4 and CO2 which are the major chemical constituents in LFG can be reacted to produce H2 by so-called catalytic dry reforming of CH4 (CDR). In this study, the impact of applying a membrane reactor (MR) for CDR is investigated in terms of energy, economic, and environmental aspects (3E). Due to the intrinsic limitation of an MR being able to operate at lower temperature than the temperature of a conventional chemical reactor (packed-bed reactor, PBR), two different process configurations are invented for an MR and a PBR separately using a commercial process simulator. Based on different process configurations, comparative techno-economic analysis is conducted for an MR and a PBR at the same temperature as well as different temperature. It is identified that energy efficiency and productivity of the process are related to the operating temperature which directly affects variation of CH4 and CO2 conversion. However, it turns out that operating at higher temperature is not always better than lower temperature due to the additional CO2 emissions and fuel costs. Especially, it is revealed that an MR will overcome its low operating temperature and accomplishes economic viability compared to a PBR by developing its durability and permeability.